Parking Identification System with Integration of Optical Character Recognition (OCR) and Radio Frequency Identification (RFID) - Raihan, Raihan Fadhil; Hendrick, Hendrick; Novi, Novi; -Jiun Horn, Gwo (JECCOM: International Journal of Electronics Engineering and Applied Science, 2024)
The Indonesian National Police (Polri) reported a significant increase in the number of crime cases during the period January - April 2023. Based on these conditions, an innovative security system is needed that can reduce the risk of motor vehicle theft. This tool is equipped with the help of an IP Camera and runs a program that has been made on programming software using OpenCV Python. The IP Camera is used to capture video that can be accessed on the server to process whether there is a license plate number detected and read the vehicle license plate number. This system integrates Radio Frequency Identification (RFID) and Optical Character Recognition (OCR) technology in the parking system. RFID technology will provide unique identification to each user who will enter the parking area, while OCR is used to read the license plate numbers of vehicles entering the parking area. OCR reading results are also sent to the microcontroller to be displayed on the LCD when the customer enters the parking area. The OCR reading results have a truth accuracy rate of 98.7%.